2020
DOI: 10.3389/fcimb.2020.00127
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Rapid and Sensitive Colorimetric Loop-Mediated Isothermal Amplification Assay: A Novel Technology for the Detection of Coxiella burnetii From Minimally Processed Clinical Samples

Abstract: Q fever is an important zoonotic disease caused by the bacterium Coxiella burnetii. The agent is considered as a potential agent for bioterrorism because of its low infectious dose, aerial route of transmission, resistance to drying, and many commonly used disinfectants. Humans are largely infected by the inhalation of aerosols that are contaminated with parturition products of infected animals as well as by the consumption of unpasteurized milk products. Thus, rapid and accurate detection of C. burnetii in sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The results indicated that the time required for the LAMP chamber to reach a temperature of 60 °C was only 32 s (standard deviation of 2.1705). Furthermore, Figure 9 shows that the temperature in the LAMP chamber was maintained between 57 and 63 °C, which is the temperature range required for a stable reaction [ 15 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the time required for the LAMP chamber to reach a temperature of 60 °C was only 32 s (standard deviation of 2.1705). Furthermore, Figure 9 shows that the temperature in the LAMP chamber was maintained between 57 and 63 °C, which is the temperature range required for a stable reaction [ 15 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Detection of C. burnetii using loop-mediated isothermal amplification (LAMP) assay [ 43 , 44 ] is rapid and comparable to real-time PCR. The positive detection is based on a change of colour in the reaction mix after 30 min incubation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the UR-qPCR proposed in this study has the advantages of being rapid, with less than 20 min reaction time, and sensitive, at 100% sensitivity compared to other real-time PCR systems. The UR-qPCR and the crude DNA preparation [ 44 ] together will take less than 30 min for the detection of C. burnetii on-site.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the UR-qPCR proposed in this study has the advantages of being rapid, with less than 20 min reaction time, and sensitive, at 100% sensitivity compared to other realtime PCR systems. The UR-qPCR and the crude DNA preparation [39] together will take less than 30 min for the detection of C. burnetii on-site.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, UR-qPCR could be used for on-site conformational diagnosis of Q fever, for the prompt control of milk, blood, or serum samples. Detection of C. burnetii using loop-mediated isothermal ampli cation (LAMP) assay [38,39] is rapid and comparable to real-time PCR. The positive detection is based on change of colour in the reaction mix after 30 min incubation.…”
Section: Discussionmentioning
confidence: 99%